Peningkatan Return Saham dan Kinerja Keuangan melalui Corporate Social Responsibility dan Good Corporate Governance - Sugiyanto, Eviatiwi Kusumaningtyas (Jurnal Ilmu Ekonomi ASET, 2011)
The purpose of this research was to find an empiric proof and analysisthat stock return and financial performance of the companies could be improved throughCorporate Social Responsibility (CSR) and Good Corporate Governance (GCG) at TheIndonesian Capital Market. Population of this research were companies that go publicat Indonesia Capital Market. Technic Sampling used purposive sampling, and found 62companies. This companies then were divided into two categories (big and small companies)according to its total assets. And the hypotheses were tested using Structural EquationModeling (SEM) with Partial Least Square (PLS) program. The result showed that (1)CSR had a significant positive effect towards stock return in big companies categorized,while small companies categorized had a significant negative effect of it, (2) GCG hadno significant effect towards stock return in both categories, (3) Financial performancehad no significant effect towards stock return in big companies categorized, but it had apositive significant effect towards it in those small, (4) CSR had a significant positiveeffect towards financial performance in big companies categorized, whereas in smallcompanies it could not be found, (5) GCG had no significant effect towards financialperformance in both categories, (6) as well as the GCG had no significant effect towardsCSR in both categories.Keywords: corporate social responsibility, good corporate governance, stock return,and financial performance.